Upper airways differences between Pierre Robin sequence and Treacher Collins syndrome - Costa, Lucas Antonio da (2021)
Introduction: Pierre Robin Sequence (PRS) and Treacher Collins Syndrome (TCS) are congenital disorders and the subjects may demonstrate similar clinical findings. Risk is equally common in male and female for both conditions. TCS is associated with alterations in the lower and upper airways and is distinct from PRS. The goal of this study was to compare the morphology pharynx taking account of volumes of segments (Nasal cavity, nasopharynx and oropharynx) and minimum sectional area of TCS and patients with non-syndromic PRS. Methods: PRS group were composed by 14 patients (5 male, 9 female) and TCS group formed by 14 patients (6 male, 8 female). Pre-orthodontic cone-beam computed tomography (CBCT) exams of all individuals were evaluated using Mimics Innovation Suite 21.0 (Materialize, Leuven, Belgium). The pharynx was divided into 3 sections: nasopharynx, oropharynx and the hypopharynx. After delimiting the regions, the total volume, nasal cavity volume, nasopharyngeal volume, oropharynx volume and minimum sectional area were determined for each patient at both conditions. Statistical analyzes were performed using Wilcoxon test for independent, paired, non-parametric data for comparative analysis of variables between the conditions PRS and TCS. The mean values and standard deviation of the variables were also determined for the PRS and TCS groups. Values of p < 0.05 were considered significant in all cases. Results: The age of PRS group range from 6 to 23 years old with a mean of 11.07±5.12 years, and at TCS group age were between 6 to 20 years with a mean of 12.00±4.50 years. Regarding the volumes of the segments of the upper airways, when comparing PRS and TCS, a significant difference was observed in total volume (p=0.0494), in nasal cavity volume (p=0.0085), in nasopharynx volume (p=0.0166) and in the minimum section area (p=0.0166). No difference was observed in the oropharynx volume (p = 0.8077). total volume, nasal cavity volume, nasopharynx volume and minimum sectional area were higher in PRS patients than in TCS patients. Conclusion: Patients with TCS have greater involvement of the upper airways with significant loss of total, nasal cavity and nasopharynx volumes compared to patients with non-syndromic PRS.